Fatigue after Stroke: The Patient's Perspective - Victoria Louise Barbour; Gillian Elizabeth Mead (Stroke Research and Treatment)
Background. Fatigue after stroke is common and distressing to patients. Aims. Our aims were to explore patients' perceptions of post-stroke fatigue, including the causes of fatigue and the factors that alleviate fatigue, in a mixed methods study. Results. We interviewed 15 patients who had had a stroke and were inpatients on stroke rehabilitation wards. A substantial proportion of patients reported that their fatigue started at the time of their stroke. Various different factors were reported to improve fatigue, including exercise, good sleep, rehabilitation and rest. Fatigue influences patients' sense of “control” after their stroke. Conclusion. Our results are consistent with the possibility that poststroke fatigue might be triggered by factors that occur at the time of the stroke (e.g., the stroke lesion itself, or admission to hospital) and then exacerbated by poor sleep and boredom. These factors should be considered when developing complex interventions to improve post-stroke fatigue.